Preparation method of walnut shell-based hard carbon negative electrode material

Through optimized preparation methods and post -processing techniques, the walnut shell is made of high -performance walnut shell -based hard carbon negative electrode materials, which solves the problem of poor electronic chemical performance and short circulation life of the existing hard carbon material, and has achieved higher a higher life. Sodium storage capacity and capacity maintenance rate.

CN119349547APending Publication Date: 2025-01-24SUZHOU PUCHANG NEW ENERGY CO LTD

Patent Information

Application Number
CN202411471098.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing hard carbon negative electrode materials have high irreversible capacity, poor electrochemical performance, and short cycle life, which limits their application fields.

Method used

Using walnut shells as raw materials, the hard carbon precursor is prepared through deionized water cleaning, drying, grinding, carbonization, pickling, drying and other steps, and is then calcined and carbonized at high temperature under nitrogen protection, and finally introduced through plasma treatment Functional groups such as thiol and perfluorononyl epoxy compounds were modified to obtain walnut shell-based hard carbon negative electrode materials.

Benefits of technology

It significantly improves the performance of hard carbon negative materials, enhances its hydrophobicity and chemical stability, improves the interface compatibility between the battery's infiltration and the electrode and electrode and the electrolyte in the electrolyte, thereby improving the capacity of sodium storage and Capacity maintenance rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005094725680000071
    Figure BDA0005094725680000071
  • Figure BDA0005094725680000081
    Figure BDA0005094725680000081
Patent Text Reader

Abstract

The invention discloses a preparation method of a walnut shell-based hard carbon negative electrode material. Through optimized plasma treatment reaction conditions, a sulfydryl-containing hard carbon material and a perfluorononyl epoxy compound are subjected to a sulfydryl-epoxy reaction, and the sulfydryl-epoxy reaction and glycidyl trimethyl ammonium chloride are subjected to a sulfydryl-epoxy reaction, so that the hard carbon material containing perfluorononyl and quaternary ammonium salt is obtained, and the performance of the hard carbon negative electrode material can be remarkably improved; by introducing perfluorononyl and quaternary ammonium salt, the surface property of the hard carbon material can be changed, and the hydrophobicity and chemical stability of the hard carbon material are improved, so that the wettability of the battery in an electrolyte is improved, and the interfacial compatibility between an electrode and the electrolyte is improved; the introduction of the functional groups may increase the active sites of the hard carbon material, thereby improving the sodium storage capacity of the hard carbon material. The introduction of perfluorononyl and quaternary ammonium salt may enhance the adsorption capacity of the hard carbon material to sodium ions, thereby improving the initial coulombic efficiency and capacity retention rate of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hard carbon negative electrode materials, in particular to a method for preparing a walnut shell-based hard carbon negative electrode material. Background Art

[0002] Hard carbon is a type of carbon that is difficult to graphitize and has an isotropic structure. It is precisely because of this amorphous structural feature that hard carbon has the advantages of long cycle life, excellent rate performance, good stability during high current charge and discharge cycles, and high reversible specific capacity as an electrode material. Hard carbon negative electrode materials are more suitable for high-power power fields.

[0003] Chinese patent CN116553514A: relates to a method for preparing a coconut shell-based hard carbon material and a sodium ion battery, and provides an application of regulating the oxygen content in the material during the coconut shell processing process to improve the electrochemical performance of coconut shell-based hard carbon materials. A method for pretreating biomass coconut shells to prepare hard carbon materials is also provided. A variety of pretreatment methods are proposed to treat biomass hard carbon precursor coconut shells to solve the problems of low specific capacity and poor cycle stability of biomass hard carbon. The pretreatment method provided can effectively remove impurities in biomass, or can effectively improve the cross-linked structure of the coconut shell precursor to provide certain conditions for the subsequent formation of more closed pores.

[0004] Chinese patent CN116443852A: belongs to the field of battery material electrode and its preparation technology. Provided is a method for preparing Torreya grandis shell-based hard carbon negative electrode material, using Torreya grandis shell as raw material, washing, drying, crushing, acid washing, washing, drying, pre-carbonizing at 350-700℃, sintering at 1100-1500℃ under inert atmosphere, and then crushing and screening to obtain Torreya grandis-based hard carbon negative electrode material.

[0005] Chinese patent CN117142456B: discloses an apricot shell-based battery hard carbon material and its preparation method and application, by first crushing the apricot shell, removing the fine powder <1μm to a weight content of no more than 5%, and then sequentially performing acid treatment, heat treatment, mixed sintering with a thermoplastic carbon precursor, demagnetization treatment, and carbon coating treatment to obtain the apricot shell-based battery hard carbon material. When biomass raw materials are used as negative electrode materials, the problem of poor consistency of biomass raw materials from different sources and types is caused by differences in pretreatment methods. A method for preparing battery negative electrode materials is proposed for apricot shell-based raw materials.

[0006] However, the hard carbon negative electrode materials prepared by the existing public technology generally have high irreversible capacity and poor electrochemical performance; the cycle life is short, which limits its application field. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a walnut shell-based hard carbon negative electrode material in view of the deficiencies in the prior art.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] A method for preparing a walnut shell-based hard carbon negative electrode material, the operating steps of which are:

[0010] S1: Wash the walnut shells with deionized water for 3-5 times, dry them at 100-120°C for 8-12h, grind them into powder, and sieve them;

[0011] S2: placing the walnut shell powder into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;

[0012] S3: placing the hard carbon precursor in a hydrochloric acid solution with a mass concentration of 10-20%, heating and washing, then washing with boiling water for 3-5 times, and drying at 100-120° C. for 20-28 hours;

[0013] S4: carbonizing the dried hard carbon precursor under the protection of nitrogen to obtain a hard carbon material;

[0014] S5: weigh 20-30 parts of hard carbon material, 1-5 parts of conductive carbon black, 1-3 parts of polyvinylidene fluoride, and 80-100 parts of solvent by weight, mix and stir evenly to obtain a mixed solution;

[0015] S6: Use an electric coating machine to evenly coat the mixed solution on the copper foil, heat it to 60-80℃ and dry it for 5-8h;

[0016] S7: The dried copper foil is cut into circular electrode sheets by a manual punch, which are pressed by a hydraulic press, dried at 90-110° C. for 10-15 h, and post-treated to obtain a walnut shell-based hard carbon negative electrode material.

[0017] Preferably, the walnut shell powder has a sieved particle size of 300-400 μm.

[0018] Preferably, the temperature of the tubular carbonization furnace is controlled at 500-600° C., and the insulation time is 50-90 minutes.

[0019] Preferably, the washing temperature of the hydrochloric acid solution is 60-70°C and the washing time is 8-12h.

[0020] Preferably, the carbonization temperature is 1000-1200° C. and the time is 90-150 min.

[0021] Preferably, the solvent is N-methylpyrrolidone.

[0022] Preferably, the pressure of the oil press is controlled at 6-10 MPa.

[0023] Preferably, the post-processing steps of the walnut shell-based hard carbon negative electrode material are:

[0024] H1: The walnut shell-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce a thiol group (-SH), wherein the thiol-containing gas is thioglycolic acid, and the flow rate range is 0.5-2L / min; thiol-containing hard carbon is obtained;

[0025] H2: by mass: 60-80 parts of mercaptolated hard carbon, 20-30 parts of perfluorononyl epoxy compound, 4-7 parts of glycidyl trimethylammonium chloride, 0.1-1 parts of catalyst lanthanum trifluoromethanesulfonate, and 800-1200 parts of tetrahydrofuran are added into a stirred tank to carry out Michael addition reaction, and after the reaction is completed, filter;

[0026] H3: After filtration, it was washed with deionized water and tetrahydrofuran and dried under vacuum at 60-70°C.

[0027] Preferably, the radio frequency power is 60-100 W, and the treatment time is 20-40 min.

[0028] Preferably, the reaction temperature is 45-65°C and the reaction time is 2-4h.

[0029] Reaction mechanism

[0030] Through optimized plasma treatment reaction conditions, the mercapto-containing hard carbon material reacts with a perfluorononyl epoxy compound for a mercapto-epoxy reaction, and reacts with glycidyl trimethylammonium chloride for a mercapto-epoxy reaction, thereby obtaining a hard carbon material containing a perfluorononyl group and a quaternary ammonium salt.

[0031] Technical Effects

[0032] The present invention provides a method for preparing a walnut shell-based hard carbon negative electrode material. Compared with the prior art, the present invention has the following significant effects:

[0033] 1. The present invention uses low-cost walnut shells as raw materials to prepare hard carbon electrode negative electrode materials, which reduces production costs and realizes a green and environmentally friendly production process;

[0034] 2. Through optimized plasma treatment reaction conditions, the thiol-containing hard carbon material reacts with perfluorononyl epoxy compounds to form a thiol-epoxy reaction, and reacts with glycidyltrimethylammonium chloride to form a thiol-epoxy reaction to obtain a hard carbon material containing perfluorononyl and quaternary ammonium salt, which can significantly improve the performance of the hard carbon negative electrode material; the introduction of perfluorononyl and quaternary ammonium salt can change the surface properties of the hard carbon material, increase its hydrophobicity and chemical stability, which helps to improve the wettability of the battery in the electrolyte, thereby improving the interfacial compatibility between the electrode and the electrolyte; the introduction of these functional groups may increase the active sites of the hard carbon material, thereby improving its sodium storage capacity; the hard carbon material has diverse structures and good conductivity, and its sodium storage capacity can be further improved by surface functionalization; the introduction of perfluorononyl and quaternary ammonium salt may enhance the adsorption capacity of the hard carbon material for sodium ions, thereby improving the first coulombic efficiency and capacity retention rate of the battery. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with preferred embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0036] Example test method:

[0037] Electrochemical performance test: After the walnut shell-based hard carbon negative electrode material was assembled into a battery, the first coulombic efficiency was tested at a current density of 100 mA / g using a Land CT-2001C electrochemical workstation; the capacity retention rate was tested after 100 cycles at a current density of 100 mA / g using an Arbin BT-2000 electrochemical workstation.

[0038] Example 1

[0039] A method for preparing a walnut shell-based hard carbon negative electrode material, the operating steps of which are:

[0040] S1: Wash the walnut shells with deionized water three times, dry them at 100 °C for 8 h, grind them into powder, and sieve them;

[0041] S2: placing the walnut shell powder into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;

[0042] S3: placing the hard carbon precursor in a hydrochloric acid solution with a mass concentration of 10%, heating and washing, then washing with boiling water for 3 times, and drying at 100°C for 20h;

[0043] S4: carbonizing the dried hard carbon precursor under the protection of nitrogen to obtain a hard carbon material;

[0044] S5: Weigh 20 g of hard carbon material, 1 g of conductive carbon black, 1 g of polyvinylidene fluoride, and 80 g of solvent, mix and stir evenly to obtain a mixed solution;

[0045] S6: Use an electric coating machine to evenly coat the mixed solution on the copper foil, heat it to 60°C and dry it for 5 hours;

[0046] S7: The dried copper foil is cut into circular electrode sheets using a manual punch, which are pressed under an oil press, dried at 90° C. for 10 h, and post-treated to obtain a walnut shell-based hard carbon negative electrode material.

[0047] The sieved particle size of the walnut shell powder is 300 μm.

[0048] The temperature of the tubular carbonization furnace is controlled at 500° C., and the insulation time is 50 minutes.

[0049] The washing temperature of the hydrochloric acid solution is 60°C and the washing time is 8 hours.

[0050] The carbonization temperature is 1000° C. and the time is 90 minutes.

[0051] The solvent is N-methylpyrrolidone.

[0052] The pressure of the oil press is controlled at 6MPa.

[0053] The post-processing steps of the walnut shell-based hard carbon negative electrode material are as follows:

[0054] H1: The walnut shell-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce a thiol group (-SH), wherein the thiol-containing gas is thioglycolic acid, and the flow range is 0.5L / min; thiol-containing hard carbon is obtained;

[0055] H2: 60 g of mercaptolated hard carbon, 20 g of perfluorononyl epoxide, 4 g of glycidyl trimethylammonium chloride, 0.1 g of catalyst lanthanum trifluoromethanesulfonate, and 800 g of tetrahydrofuran were added into a stirred tank for Michael addition reaction. After the reaction was completed, the reaction was filtered;

[0056] H3: After filtration, it was washed with deionized water and tetrahydrofuran and dried in vacuum at 60°C.

[0057] The radio frequency power is 60W and the treatment time is 20min.

[0058] The reaction temperature is 45°C and the reaction time is 2h.

[0059] Example 2

[0060] A method for preparing a walnut shell-based hard carbon negative electrode material, the operating steps of which are:

[0061] S1: Wash the walnut shells with deionized water for 4 times, dry them at 105 °C for 9 h, grind them into powder, and sieve them;

[0062] S2: placing the walnut shell powder into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;

[0063] S3: placing the hard carbon precursor in a hydrochloric acid solution with a mass concentration of 15%, heating and washing, then washing with boiling water for 4 times, and drying at 105°C for 22h;

[0064] S4: carbonizing the dried hard carbon precursor under the protection of nitrogen to obtain a hard carbon material;

[0065] S5: Weigh 23 g of hard carbon material, 2 g of conductive carbon black, 2 g of polyvinylidene fluoride, and 85 g of solvent, mix and stir evenly to obtain a mixed solution;

[0066] S6: Use an electric coating machine to evenly coat the mixed solution on the copper foil, heat it to 65°C and dry it for 6 hours;

[0067] S7: The dried copper foil is cut into circular electrode sheets using a manual punch, which are pressed under an oil press, dried at 95° C. for 12 h, and post-treated to obtain a walnut shell-based hard carbon negative electrode material.

[0068] The sieved particle size of the walnut shell powder is 300 μm.

[0069] The temperature of the tubular carbonization furnace is controlled at 540° C., and the insulation time is 60 minutes.

[0070] The washing temperature of the hydrochloric acid solution is 65°C and the washing time is 9 hours.

[0071] The carbonization temperature is 1050° C. and the time is 110 min.

[0072] The solvent is N-methylpyrrolidone.

[0073] The pressure of the oil press is controlled at 7MPa.

[0074] The post-processing steps of the walnut shell-based hard carbon negative electrode material are as follows:

[0075] H1: The walnut shell-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce mercapto groups (-SH), wherein the mercapto-containing gas is thioglycolic acid, and the flow rate range is 1L / min; mercapto hard carbon is obtained;

[0076] H2: 65 g of mercaptolated hard carbon, 23 g of perfluorononyl epoxide, 5 g of glycidyl trimethylammonium chloride, 0.5 g of catalyst lanthanum trifluoromethanesulfonate, and 900 g of tetrahydrofuran were added to a stirred tank for Michael addition reaction. After the reaction was completed, the reaction was filtered;

[0077] H3: After filtration, it was washed with deionized water and tetrahydrofuran and dried in vacuum at 65°C.

[0078] The radio frequency power is 70W and the treatment time is 25 minutes.

[0079] The reaction temperature is 50°C and the reaction time is 3 hours.

[0080] Example 3

[0081] A method for preparing a walnut shell-based hard carbon negative electrode material, the operating steps of which are:

[0082] S1: The walnut shells were washed with deionized water for 4 times, dried at 115 °C for 11 h, ground into powder, and sieved;

[0083] S2: placing the walnut shell powder into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;

[0084] S3: placing the hard carbon precursor in a hydrochloric acid solution with a mass concentration of 15%, heating and washing, then washing with boiling water for 4 times, and drying at 115°C for 26 hours;

[0085] S4: carbonizing the dried hard carbon precursor under the protection of nitrogen to obtain a hard carbon material;

[0086] S5: Weigh 28 g of hard carbon material, 4 g of conductive carbon black, 2 g of polyvinylidene fluoride, and 95 g of solvent, mix and stir evenly to obtain a mixed solution;

[0087] S6: Use an electric coating machine to evenly coat the mixed solution on the copper foil, heat it to 75°C and dry it for 7 hours;

[0088] S7: The dried copper foil is cut into circular electrode sheets using a manual punch, which are pressed under an oil press, dried at 105° C. for 14 h, and post-treated to obtain a walnut shell-based hard carbon negative electrode material.

[0089] The sieved particle size of the walnut shell powder is 400 μm.

[0090] The temperature of the tubular carbonization furnace is controlled at 580° C., and the insulation time is 80 minutes.

[0091] The washing temperature of the hydrochloric acid solution is 65°C and the washing time is 11 hours.

[0092] The carbonization temperature is 1150° C. and the time is 130 min.

[0093] The solvent is N-methylpyrrolidone.

[0094] The pressure of the oil press is controlled at 9MPa.

[0095] The post-processing steps of the walnut shell-based hard carbon negative electrode material are as follows:

[0096] H1: The walnut shell-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce mercapto groups (-SH), wherein the mercapto-containing gas is thioglycolic acid, and the flow rate range is 1.5 L / min; mercapto hard carbon is obtained;

[0097] H2: 75 g of mercaptolated hard carbon, 28 g of perfluorononyl epoxide, 6 g of glycidyl trimethylammonium chloride, 0.8 g of catalyst lanthanum trifluoromethanesulfonate, and 1100 g of tetrahydrofuran were added to a stirred tank for Michael addition reaction. After the reaction was completed, the reaction was filtered;

[0098] H3: After filtration, it was washed with deionized water and tetrahydrofuran and dried in vacuum at 65°C.

[0099] The radio frequency power is 90W and the treatment time is 35 minutes.

[0100] The reaction temperature is 60°C and the reaction time is 3 hours.

[0101] Example 4

[0102] A method for preparing a walnut shell-based hard carbon negative electrode material, the operating steps of which are:

[0103] S1: Wash the walnut shells with deionized water for 5 times, dry them at 120 °C for 12 h, grind them into powder, and sieve them;

[0104] S2: placing the walnut shell powder into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor;

[0105] S3: placing the hard carbon precursor in a hydrochloric acid solution with a mass concentration of 20%, heating and washing, then washing with boiling water for 5 times, and drying at 120°C for 28h;

[0106] S4: carbonizing the dried hard carbon precursor under the protection of nitrogen to obtain a hard carbon material;

[0107] S5: Weigh 30 g of hard carbon material, 5 g of conductive carbon black, 3 g of polyvinylidene fluoride, and 100 g of solvent, mix and stir evenly to obtain a mixed solution;

[0108] S6: Use an electric coating machine to evenly coat the mixed solution on the copper foil, heat it to 80°C and dry it for 8 hours;

[0109] S7: The dried copper foil is cut into circular electrode sheets using a manual punch, which are pressed under an oil press, dried at 110° C. for 15 h, and post-treated to obtain a walnut shell-based hard carbon negative electrode material.

[0110] The sieved particle size of the walnut shell powder is 400 μm.

[0111] The temperature of the tubular carbonization furnace is controlled at 600° C., and the insulation time is 90 minutes.

[0112] The washing temperature of the hydrochloric acid solution is 70°C and the washing time is 12 hours.

[0113] The carbonization temperature is 1200° C. and the time is 150 min.

[0114] The solvent is N-methylpyrrolidone.

[0115] The pressure of the oil press is controlled at 10 MPa.

[0116] The post-processing steps of the walnut shell-based hard carbon negative electrode material are as follows:

[0117] H1: The walnut shell-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce mercapto groups (-SH), wherein the mercapto-containing gas is thioglycolic acid, and the flow rate range is 2L / min; mercapto hard carbon is obtained;

[0118] H2: 80g of mercaptolated hard carbon, 30g of perfluorononyl epoxide, 7g of glycidyl trimethylammonium chloride, 1g of catalyst lanthanum trifluoromethanesulfonate, and 1200g of tetrahydrofuran were added into a stirred tank for Michael addition reaction. After the reaction was completed, the reaction was filtered;

[0119] H3: After filtration, it was washed with deionized water and tetrahydrofuran and dried under vacuum at 70°C.

[0120] The radio frequency power is 100W and the processing time is 40min.

[0121] The reaction temperature is 65°C and the reaction time is 4 hours.

[0122] Comparative Example 1

[0123] In this example, the walnut shell-based hard carbon negative electrode material is not post-treated, and the rest is the same as in Example 1.

[0124] Comparative Example 2

[0125] In this example, no perfluorononyl epoxy compound is added during the post-treatment of the walnut shell-based hard carbon negative electrode material, and the rest is the same as in Example 1.

[0126] Comparative Example 3

[0127] In this example, no glycidyl trimethyl ammonium chloride is added during the post-treatment of the walnut shell-based hard carbon negative electrode material, and the rest is the same as in Example 1.

[0128] Test results:

[0129]

[0130]

[0131] Through the data analysis of the above embodiments and comparative examples, the walnut shell-based hard carbon negative electrode material prepared by the present invention has a higher first coulombic efficiency and capacity retention rate.

[0132] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a walnut shell-based hard carbon negative electrode material, the operating steps of which are: S1: Wash the walnut shells with deionized water for 3-5 times, dry them at 100-120°C for 8-12h, grind them into powder, and sieve them; S2: placing the walnut shell powder into a tubular carbonization furnace and calcining it at high temperature under the protection of nitrogen to obtain a hard carbon precursor; S3: placing the hard carbon precursor in a hydrochloric acid solution with a mass concentration of 10-20%, heating and washing, then washing with boiling water for 3-5 times, and drying at 100-120° C. for 20-28 hours; S4: carbonizing the dried hard carbon precursor under the protection of nitrogen to obtain a hard carbon material; S5: weigh 20-30 parts of hard carbon material, 1-5 parts of conductive carbon black, 1-3 parts of polyvinylidene fluoride, and 80-100 parts of solvent by weight, mix and stir evenly to obtain a mixed solution; S6: Use an electric coating machine to evenly coat the mixed solution on the copper foil, heat it to 60-80℃ and dry it for 5-8h; S7: The dried copper foil is cut into circular electrode sheets by a manual punch, which are pressed by a hydraulic press, dried at 90-110° C. for 10-15 h, and post-treated to obtain a walnut shell-based hard carbon negative electrode material.

2. The method for preparing a walnut shell-based hard carbon negative electrode material according to claim 1, characterized in that: The sieved particle size of the walnut shell powder is 300-400 μm.

3. The method for preparing a walnut shell-based hard carbon negative electrode material according to claim 1, characterized in that: The temperature of the tubular carbonization furnace is controlled at 500-600° C., and the insulation time is 50-90 minutes.

4. The method for preparing a walnut shell-based hard carbon negative electrode material according to claim 1, characterized in that: The washing temperature of the hydrochloric acid solution is 60-70°C and the washing time is 8-12h.

5. The method for preparing a walnut shell-based hard carbon negative electrode material according to claim 1, characterized in that: The carbonization temperature is 1000-1200°C and the time is 90-150 minutes.

6. The method for preparing a walnut shell-based hard carbon negative electrode material according to claim 1, characterized in that: The solvent is N-methylpyrrolidone.

7. The method for preparing a walnut shell-based hard carbon negative electrode material according to claim 1, characterized in that: The pressure of the oil press is controlled at 6-10MPa.

8. The method for preparing a walnut shell-based hard carbon negative electrode material according to claim 1, characterized in that: The post-processing steps of the walnut shell-based hard carbon negative electrode material are as follows: H1: The walnut shell-based hard carbon negative electrode material is treated by a radio frequency plasma generator to introduce a thiol group (-SH), wherein the thiol-containing gas is thioglycolic acid, and the flow rate range is 0.5-2L / min; thiol-containing hard carbon is obtained; H2: by mass: 60-80 parts of mercaptolated hard carbon, 20-30 parts of perfluorononyl epoxy compound, 4-7 parts of glycidyl trimethylammonium chloride, 0.1-1 parts of catalyst lanthanum trifluoromethanesulfonate, and 800-1200 parts of tetrahydrofuran are added into a stirred tank to carry out Michael addition reaction, and after the reaction is completed, filter; H3: After filtration, it was washed with deionized water and tetrahydrofuran and dried under vacuum at 60-70°C.

9. The method for preparing a walnut shell-based hard carbon negative electrode material according to claim 8, characterized in that: The radio frequency power is 60-100W, and the treatment time is 20-40min.

10. The method for preparing a walnut shell-based hard carbon negative electrode material according to claim 8, characterized in that: The reaction temperature is 45-65°C and the reaction time is 2-4h.

Citation Information

Patent Citations

  • Preparation method of torreya grandis shell-based hard carbon negative electrode material

    CN116443852A

  • Preparation method of coconut shell-based hard carbon material and sodium ion battery

    CN116553514A

  • A kind of apricot shell-based battery hard carbon material and its preparation method and application

    CN117142456B

Cited By

  • A kind of acid-assisted hydrothermal pretreatment regulates walnut shell trinucleus composition hard carbon negative material and its preparation method and application

    CN122916106A